Relationship of Hypertension Control Factors with Blood Pressure in Hypertension Patients at Pandanwangi Primary Health CareMalang - Devi Rahmaningrum Wardani, - (Universitas Airlangga, 2021)
Introduction: Hypertension is a common cause of the increase of mortality rate and morbidiety in the community. Complications of hypertension cause approximately 9.4 deaths around the world each year. The purpose of this study is to analyze the relationship of factors controlling hypertension with blood pressure.Methods:This study useda descriptive correlational design with the cross sectional approach. The study population was patients with hypertension in Puskesmas Pandanwangi Malang City. The sample used as many as 96 people based on purposive sampling technique. The instruments used were questionnaire sheets, spyghmomanometer and stethoscope. Analysis using the test Spearman rho test with a significance level of p <0.005.Result:The results showed there are a relationship between knowledge (p = 0.000 and r = 0.778), attitude (p = 0.000 and r = 0.626), diet (p = 0.000 and r = 0.609), physical activity (p = 0.000 and r = 0.449), family support (p = 0.000 and r = 0.607), and medication adherence (p = 0.000 and r = 0.726) with blood pressure .Conclusion:There is a significant relationship and the direction between the knowledge, attitude, diet, physical activity, family support, and medication adherence with blood pressure.Cite this as:Wardani, D.R., Wahyuni, E. D., & Ni’mah, L.(2021). Relationship of Hypertension Control Factors with Blood Pressure in Hypertension Patients at Pandanwangi Primary Health CareMalang.Crit. Méd. Surgical. Nurs. J,10(1), xx-xx.1.INTRODUCTIONPatients Attention to Non-Communicable Diseases (PTM) is currently increasing along with the increasing frequency of PTM occurrences in the community. Hypertension is one of the non-communicable diseases that has increased the incidence in society. The increase in the incidence of hypertension is related to a lifestyle, including smoking, alcohol consumption, physical activity and less consumption of fruits and vegetables. Hypertension is also called the silent killer because it is one of the causes of increased morbidity and mortality. This shows how important hypertension is to be overcome, one way is to control blood pressure to keep it in a normal state. Blood pressure control must be done so that there is no increase in the incidence of hypertension.(Maharani & Syafrandi, 2017). However, until now the relationship between these factors and blood pressure has not been explained.World Health Organization(WHO) states that hypertension contributes to nearly 9.4 million deaths from cardiovascular disease every year (WHO, 2013). WHO data for 2015 shows that around 1.13 billion people in the world have hypertension. The number CRITICAL MEDICAL AND SURGICALNURSING JOURNALVol. 10, No. 1, April 2021Journal Homepage: https://e-journal.unair.ac.id/CMSNJ